Spatial and temporal dimensions of agricultural land use changes, 2001–2012, East-Central Iowa. (October 2016) - Ren, Jie; Campbell, James B.; Shao, Yang
Abstract: In central regions of the U. S. Corn Belt, agricultural production since 2001 has changed in response to federal policies implemented to encourage production of biofuels. Such changes have influenced agricultural practices, land uses, and their spatial character. This study examines site-specific temporal and spatial patterns of agricultural land use dynamics from 2001 to 2012 in a nine-county region of East-Central Iowa using the United States Department of Agriculture National Agricultural Statistics Service Cropland Data Layer. Results indicate that increases in corn production in response to US biofuel policies and high grain prices have been achieved mainly by altering crop rotation patterns. These changes may be correlated with market forces, although variations suggest a multiplicity of causes. This study also examines spatial relationships between cultivated fields and crop rotation practices with respect to underlying soils and terrain. Intensity of cultivated land use depends on topographic and pedologic properties, although motivations and constraints perceived by producers and managers as they plan their use of landscapes are important. The most intensively cultivated lands have shallower slopes and fewer pedologic limitations than others, and corn was planted in higher quality soil while soybeans were moved to lesser quality soils. Declining acreage in the Conservation Reserve Program since 2007 indicates that they may be used for other crops displaced by corn. Highlights: We examined changes of cultivated cropland and crop rotation sequences on a pixel-by-pixel basis. We examined spatial relationships between cultivated fields, crop rotation practices, and underlying soils and terrain. Intensity of cultivated land use depended on topographic and pedologic properties. Expansion of corn production after 2007 was realized by altering crop rotation patterns at pixel level.